Rubber composition for fender and fender using same
By using a specific ethylene-α-olefin copolymer rubber with ethylene content between 65% to 80% and a diene content, the rubber composition for fenders achieves high hardness with excellent cushioning performance and processability, addressing the manufacturing challenges posed by increased carbon black content.
Patent Information
- Application Number
- JP2021065956
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-08
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-04-08
AI Technical Summary
Existing rubber compositions for fenders face challenges in maintaining high rubber hardness while ensuring excellent cushioning performance and processability, particularly when increasing the proportion of carbon black to enhance hardness, which can lead to increased viscosity and reduced elongation, making it difficult to manufacture fenders efficiently.
Incorporating a specific ethylene-α-olefin copolymer rubber with an ethylene content of 65% to 80% by mass and a diene content in a predetermined ratio, along with carbon black, to balance the physical properties and maintain processability even when increasing rubber hardness.
The solution allows for the production of fenders with enhanced cushioning performance and improved processability, even with increased carbon black content, by balancing elongation, tensile strength, and compression set, thus facilitating efficient manufacturing.
Smart Images

Figure 0007620847000001 
Figure 0007620847000002 
Figure 0007620847000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber composition for a fender for forming a fender that is installed, for example, on a quay or the like and absorbs the energy of a ship or the like coming alongside, and to a fender at least a part of which, for example a support leg or the like, is made of a cross-linked product of the rubber composition for a fender. [Background technology]
[0002] In recent years, there are cases where fenders are required to have a high rubber hardness in the cross-linked product (see Patent Document 1, etc.). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-222830 A [Patent Document 2] Increasing the rubber hardness of the cross-linked product can provide the fender with high shock-absorbing performance that can accommodate larger ships, etc. It can also make the fender smaller, ensuring good shock-absorbing performance without taking up space at the installation site, and reducing the amount of material used to reduce production costs.
[0004] In order to increase the rubber hardness of the cross-linked product that forms the fender, it is common to increase the proportion of the above-mentioned filler, particularly carbon black, in the rubber composition for the fender, which is prepared by blending a cross-linking component for cross-linking the rubber, a filler, etc., with the rubber. However, when the proportion of the filler such as carbon black is simply increased, the viscosity of the rubber composition for a fender before crosslinking increases, which may result in a decrease in processability.
[0005] Furthermore, it may become difficult to knead the various components to prepare the rubber composition for the fender, or to knead the rubber composition for the fender or mold it into any three-dimensional shape to produce the fender. For example, Patent Document 1 considers increasing the rubber hardness of a cross-linked product of a rubber composition for a fender by compounding 60 parts by mass or more of carbon black per 100 parts by mass of rubber as a filler.
[0006] In addition, examples are given in which the rubber hardness of the crosslinked product is A77, expressed in type A durometer hardness. However, Patent Document 1 does not discuss the processability of the rubber composition for fenders, and there is concern that the rubber composition for fenders and fenders themselves may not be able to be produced efficiently, particularly in the above examples.
[0007] In addition, in the rubber composition for fenders, it is important to provide the fender with good shock-absorbing performance by appropriately balancing the physical properties (rubber physical properties) of the cross-linked product, such as the rubber hardness of the cross-linked product, the elongation and tensile strength, and further the compression set. However, if the proportion of carbon black is increased solely in order to increase the rubber hardness, the elongation of the cross-linked product in particular will decrease, making it impossible to impart good shock-absorbing performance to the fender, i.e., there is a concern that the desired fender will not be realized.
[0008] The object of the present invention is to provide a rubber composition for a fender which can form a fender having excellent shock-absorbing performance even when the proportion of carbon black is increased in order to increase the rubber hardness of the cross-linked product, and which also has excellent processability, and to provide a fender at least partly made of a cross-linked product of the rubber composition for a fender. Summary of the Invention [Means for solving the problem]
[0009] The present invention is a rubber composition for a fender comprising a cross-linkable rubber, 60 parts by mass or more and 90 parts by mass or less of carbon black per 100 parts by mass of the total amount of the rubber, and a cross-linking component for cross-linking the rubber, wherein the rubber comprises an ethylene-α-olefin copolymer rubber having an ethylene content of 65% by mass or more and 80% by mass or less, in an amount of 3 parts by mass or more and 35 parts by mass or less, per 100 parts by mass of the total amount of the rubber.
[0010] The present invention also relates to a fender, at least a part of which is made of a crosslinked product of the rubber composition for a fender of the present invention. Effect of the Invention
[0011] According to the present invention, it is possible to form a fender having excellent shock-absorbing performance even when the proportion of carbon black is increased in order to increase the rubber hardness of the cross-linked product, and it is also possible to provide a rubber composition for a fender which has excellent processability, and a fender at least a part of which is made of a cross-linked product of the rubber composition for a fender. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] <Rubber composition for fender> As described above, the rubber composition for fenders of the present invention comprises a cross-linkable rubber, 60 parts by mass or more and 90 parts by mass or less of carbon black per 100 parts by mass of the total amount of the rubber, and a cross-linking component for cross-linking the rubber, and the rubber is characterized in that it contains a specific ethylene-α-olefin copolymer rubber having an ethylene content of 65% by mass or more and 80% by mass or less in an amount of 3 parts by mass or more and 35 parts by mass or less per 100 parts by mass of the total amount of the rubber.
[0013] According to the present invention, by containing the specific ethylene-α-olefin copolymer rubber in the above-mentioned predetermined ratio, it is possible to prevent the viscosity of the rubber composition for fenders from increasing even if the proportion of carbon black is increased to increase the rubber hardness of the cross-linked product. In addition, it is possible to suppress a decrease in the processability of the rubber composition for a fender. In addition, by containing the specific ethylene-α-olefin copolymer rubber in the above-mentioned predetermined ratio, the rubber properties of the cross-linked product can be appropriately balanced even if the proportion of carbon black is increased, and good cushioning performance can be imparted to the fender.
[0014] Therefore, according to the present invention, a fender having excellent shock-absorbing performance can be formed even if the proportion of carbon black is increased in order to increase the rubber hardness of the cross-linked product, and a rubber composition for a fender having excellent processability can be provided. These facts are also evident from the results of the examples and comparative examples described below. Patent Document 2 describes a rubber composition for a fender that uses 20 to 40 parts by mass of an ethylene-propylene copolymer rubber having an ethylene content of 50 to 85% by mass and 60 to 80 parts by mass of natural rubber in combination.
[0015] However, the rubber composition for fenders described in Patent Document 2 is a non-carbon black reinforcing composition that excludes carbon black in order to form fenders of any color other than black (paragraph
[0002] of Patent Document 2, etc.). Patent Document 2 does not describe at all the ethylene content or compounding ratio of the ethylene-propylene copolymer rubber in order to solve the problems that arise when the proportion of carbon black is increased.
[0016] Therefore, the description in Patent Document 2 does not teach or suggest the present invention. <Rubber> As described above, the rubber used is a specific ethylene-α-olefin copolymer rubber having an ethylene content of 65% by mass or more and 80% by mass or less, in an amount of 3 parts by mass or more and 35 parts by mass or less per 100 parts by mass of the total amount of rubber.
[0017] (Ethylene-α-olefin copolymer rubber) Of the rubbers, the ethylene content of the ethylene-α-olefin copolymer rubber is limited to the above range for the following reasons. That is, if the ethylene content is less than 65% by mass, the elongation and tensile strength of the cross-linked product will be small, particularly when the proportion of carbon black is increased, and good shock-absorbing performance may not be imparted to the fender.
[0018] On the other hand, if the ethylene content exceeds 80% by mass, the compression set of the cross-linked product increases, particularly when the proportion of carbon black is increased, and the fender may not be able to exhibit good shock-absorbing performance. In contrast, by selecting and using a specific ethylene-α-olefin copolymer rubber having an ethylene content within the above range, it is possible to appropriately balance the rubber properties of the cross-linked product even if the proportion of carbon black is increased, and to impart good shock-absorbing performance to the fender.
[0019] In order to further improve such effects, the ethylene content of the ethylene-α-olefin copolymer rubber is preferably 66% by mass or more and 77% by mass or less even within the above range. Examples of the α-olefin that constitutes the specific ethylene-α-olefin copolymer rubber together with ethylene include propylene, butene, and octene.
[0020] As the specific ethylene-α-olefin copolymer rubber, in addition to a copolymer rubber of ethylene and an α-olefin, a copolymer rubber of ethylene, an α-olefin and a diene can also be used. In particular, when a sulfur crosslinkable crosslinking component is used, it is preferable to use the latter copolymer rubber of ethylene, α-olefin and diene, and examples of the diene include ethylidene norbornene, dicyclopentadiene, 1,4-hexadiene, etc.
[0021] In addition, the α-olefin in the ethylene-α-olefin copolymer rubber containing a diene is preferably propylene or butene. Examples of specific ethylene-α-olefin copolymer rubbers include ethylene-propylene copolymer rubber (EPM), ethylene-butene copolymer rubber (EBR), ethylene-octene copolymer rubber (EOR), ethylene-propylene-butene copolymer rubber (EPBR), ethylene-propylene-diene copolymer rubber (EPDM), ethylene-butene-diene copolymer rubber (EBDM), ethylene-propylene-butene-diene copolymer rubber (EPBDM), etc., and those having an ethylene content within the aforementioned range can be selected and used.
[0022] In particular, EPDM and / or EBDM, which have excellent sulfur crosslinking properties, are preferred. EPDM As the EPDM, various copolymers obtained by copolymerizing ethylene, propylene, and diene can be used. EPDM is classified into an oil-extended type in which flexibility is adjusted by adding an extender oil, and a non-oil-extended type in which no extender oil is added, and either type of EPDM may be used in the present invention.
[0023] Specific examples of non-oil-extended EPDM having an ethylene content within the above-mentioned range include, but are not limited to, the following various EPDMs. Esprene (registered trademark) 512F (ethylene content: 65 mass%, diene content: 4.0 mass%) and 586 (ethylene content: 66 mass%, diene content: 12.5 mass%), manufactured by Sumitomo Chemical Co., Ltd.
[0024] NORDEL (registered trademark) IP3720P (ethylene content: 70% by mass, diene content: 0.6% by mass), IP3722P (ethylene content: 71% by mass, diene content: 0.5% by mass), IP3745P (ethylene content: 70% by mass, diene content: 0.5% by mass), IP3760P (ethylene content: 67% by mass, diene content: 2.2% by mass), IP4725P ( Ethylene content: 70% by mass, diene content: 4.9% by mass], IP4760P [Ethylene content: 67% by mass, diene content: 4.9% by mass], IP4770R [Ethylene content: 70% by mass, diene content: 4.9% by mass], IP4770P [Ethylene content: 70% by mass, diene content: 4.9% by mass], IP4785HM [Ethylene content: 68% by mass, diene content: 4.9% by mass], IP3722P EL [ethylene content: 71 mass%, diene content: 0.5 mass%], IP3745P EL [ethylene content: 70 mass%, diene content: 0.5 mass%], IP4770P EL [ethylene content: 70 mass%, diene content: 4.9 mass%], IP4770R EL [ethylene content: 70 mass%, diene content: 4.9 mass%].
[0025] EP51 manufactured by JSR Corporation [ethylene content: 67 mass%, diene content: 5.8 mass%]. Mitsui EPT 3092M (ethylene content: 65% by mass, diene content: 4.6% by mass), X-3012P (ethylene content: 72% by mass, diene content: 3.6% by mass), and 3092PM (ethylene content: 65% by mass, diene content: 4.6% by mass), manufactured by Mitsui Chemicals, Inc. Specific examples of oil-extended EPDM having an ethylene content within the above-mentioned range include, but are not limited to, the following various EPDMs.
[0026] Sumitomo Chemical Co., Ltd.'s Esprene 6101 (ethylene content: 70 mass%, diene content: 6.5 mass%, oil extended amount: 70 phr), 600F (ethylene content: 66 mass%, diene content: 4.0 mass%, oil extended amount: 100 phr), and 670F (ethylene content: 66 mass%, diene content: 4.0 mass%, oil extended amount: 100 phr). EP98 manufactured by JSR Corporation [ethylene content: 66 mass%, diene content: 4.5 mass%, oil extension amount: 75 phr].
[0027] Mitsui EPT X-3042E (ethylene content: 66 mass%, diene content: 4.7 mass%, oil extension amount: 120 phr) and 3062EME (ethylene content: 65 mass%, diene content: 4.5 mass%, oil extension amount: 20 phr) manufactured by Mitsui Chemicals, Inc. One or more of these non-oil-extended EPDM and / or oil-extended EPDM can be used. · EBDM As the EBDM, various copolymers obtained by copolymerizing ethylene, butene, and diene can be used.
[0028] In addition, there are two types of EBDM: oil-extended type, in which the flexibility is adjusted by adding an extender oil, and non-oil-extended type, in which no extender oil is added. Either type of EBDM may be used in the present invention. Specific examples of non-oil-extended EBDM having an ethylene content within the above range include, but are not limited to, the following EBDM: Mitsui EPT K-9720 (ethylene content: 77% by mass, diene content: 10.4% by mass) manufactured by Mitsui Chemicals, Inc.
[0029] The proportion of these specific ethylene-α-olefin copolymer rubbers, such as EPDM and / or EBDM, having an ethylene content of 65 mass% or more and 80 mass% or less, is limited to 3 mass parts or more and 35 mass parts or less per 100 mass parts of the total amount of rubber for the following reasons. That is, if the proportion of the specific ethylene-α-olefin copolymer rubber is less than this range, the above-mentioned effects of compounding the ethylene-α-olefin copolymer rubber may not be obtained.
[0030] Specifically, when the proportion of carbon black is increased in order to increase the rubber hardness of the cross-linked product, the viscosity of the rubber composition for fenders increases, and processability may decrease. In addition, the elongation of the crosslinked material may become small, making it impossible to provide the fender with good shock-absorbing properties. On the other hand, if the proportion of the specific ethylene-α-olefin copolymer rubber exceeds the above range, the tensile strength of the cross-linked product may decrease or the compression set may increase, particularly when the proportion of carbon black is increased, which may result in a decrease in the cushioning performance of the fender.
[0031] In contrast, by setting the proportion of the specific ethylene-α-olefin copolymer rubber within the above range, a fender having excellent shock-absorbing performance can be formed even if the proportion of carbon black is increased to increase the rubber hardness of the cross-linked product. In addition, a rubber composition for a fender having excellent processability can be obtained. That is, it becomes easy to knead each component to prepare the rubber composition for a fender, and to knead the rubber composition for a fender or to mold it into any three-dimensional shape to produce a fender.
[0032] In order to further improve these effects, the proportion of the specific ethylene-α-olefin copolymer rubber, even within the above range, is preferably 4 parts by mass or more, particularly 5 parts by mass or more, per 100 parts by mass of the total amount of rubber, and is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and particularly preferably 20 parts by mass or less. When an oil-extended ethylene-α-olefin copolymer rubber such as oil-extended EPDM is used, the above ratio refers to the ratio of the ethylene-α-olefin copolymer rubber itself as the solid content (rubber) contained in the oil-extended ethylene-α-olefin copolymer rubber.
[0033] (other rubber) As the other rubber to be used in combination with the ethylene-α-olefin copolymer rubber, various rubbers having crosslinkability can be used. However, in consideration of providing the fender with good shock-absorbing performance by appropriately balancing the rubber properties of the cross-linked product, the other rubbers preferred are natural rubber and isoprene rubber (IR), which has a polyisoprene structure that artificially reproduces the structure of natural rubber and is also cross-linkable.
[0034] Among these, natural rubber is preferred because it can form a fender with excellent shock-absorbing performance due to the gentle cross-linking structure between rubber molecules in the cross-linked state, and because it is easily available and the rubber composition for the fender can be produced at low cost. Examples of natural rubber include various grades of natural rubber such as TSR-20 and RSS#3, and also deproteinized natural rubber can be used.
[0035] One or more of these natural rubbers can be used. The rubbers used may be only two types, ethylene-α-olefin copolymer rubber and natural rubber (including the use of two or more types of each rubber; the same applies below), or these two types of rubber may be used in combination with another rubber. Examples of the other rubber include one or more synthetic rubbers such as styrene butadiene rubber (SBR), butadiene rubber (BR), butyl rubber (IIR), chloroprene rubber (CR), chlorosulfonated polyethylene (CSM), acrylonitrile butadiene rubber (NBR), hydrogenated acrylonitrile butadiene rubber (HNBR), acrylic rubber (ACM), fluororubber (FKM), and epichlorohydrin rubber. In addition, other ethylene-α-olefin copolymer rubbers other than those specified, such as EPDM, EBDM, and EPM, whose ethylene content is outside the above-mentioned range, can also be used.
[0036] However, in consideration of simplifying the composition and producing the rubber composition for fenders at low cost, it is preferable to use only two types of rubber in combination: a specific ethylene-α-olefin copolymer rubber having an ethylene content within the above-mentioned range, and natural rubber. When only the above two types of rubber are used in combination, the proportion of natural rubber is the remainder of the specific ethylene-α-olefin copolymer rubber.
[0037] In other words, the proportion of natural rubber is limited to 65 parts by mass or more and 97 parts by mass or less out of 100 parts by mass of the total amount of rubber, and is preferably 70 parts by mass or more, particularly 75 parts by mass or more, and even more preferably 80 parts by mass or more, and is preferably 96 parts by mass or less, and especially preferably 95 parts by mass or less. Carbon Black As the carbon black, various carbon blacks capable of functioning as a rubber filler (filling agent, reinforcing agent), such as furnace black, acetylene black, and ketjen black, can be used.
[0038] Specific examples of carbon black include, but are not limited to, the following carbon blacks: From the SEAT (registered trademark) series manufactured by Tokai Carbon Co., Ltd., SEAT 9H (SAF-HS, nitrogen adsorption specific surface area: 142 m 2 / g], SEAT 9 [SAF, nitrogen adsorption specific surface area: 142 m 2 / g], SEAT 7HM [N234, nitrogen adsorption specific surface area: 126 m2 / g], Seast 6 [ISAF, nitrogen adsorption specific surface area: 119 m 2 / g], SEAT 600 [ISAF-LS, nitrogen adsorption specific surface area: 106 m 2 / g], SEAT 5H [IISAF, nitrogen adsorption specific surface area: 99 m 2 / g], Seest KH [N399, nitrogen adsorption specific surface area: 93 m 2 / g], SEAT 3H [HAF-HS, nitrogen adsorption specific surface area: 82 m 2 / g], SEAT NH [N351, nitrogen adsorption specific surface area: 74 m 2 / g], SEAT 3 [HAF, nitrogen adsorption specific surface area: 79 m 2 / g], SEAT N [LI-HAF, nitrogen adsorption specific surface area: 74 m 2 / g], SEAT 300 [HAF-LS, nitrogen adsorption specific surface area: 84 m 2 / g], SEAT 116HM [MAF-HS, nitrogen adsorption specific surface area: 56 m 2 / g], SEAT 116 [MAF, nitrogen adsorption specific surface area: 49 m 2 / g], seast SO〔FEF, nitrogen adsorption specific surface area: 42m 2 / g], Seast V [GPF, nitrogen adsorption specific surface area: 27m 2 / g], SEAT SVH [SRF-HS, nitrogen adsorption specific surface area: 32 m 2 / g], Seest FY [SRF-HS, nitrogen adsorption specific surface area: 29 m 2 / g], SEAT S [SRF, nitrogen adsorption specific surface area: 27 m 2 / g], SEAT SP [SRF-LS, nitrogen adsorption specific surface area: 23 m 2 / g], SEAT TA [FT class, nitrogen adsorption specific surface area: 19m 2 / g]
[0039] Asahi #95 (nitrogen adsorption specific surface area: 147 m) manufactured by Asahi Carbon Co., Ltd. 2 / g], Asahi #80 [ISAF, nitrogen adsorption specific surface area: 115 m 2 / g], Asahi #70 [HAF, nitrogen adsorption specific surface area: 77 m 2 / g], Asahi #70L [Nitrogen adsorption specific surface area: 84 m 2 / g], Asahi AX-015 [Nitrogen adsorption specific surface area: 145 m 2 / g], Asahi F-200GS [Nitrogen adsorption specific surface area: 51 m 2 / g], Asahi #65 [Nitrogen adsorption specific surface area: 42 m 2 / g], Asahi #60HN [Nitrogen adsorption specific surface area: 48 m 2 / g], Asahi #60U [Nitrogen adsorption specific surface area: 43 m 2 / g], Asahi #55 [Nitrogen adsorption specific surface area: 26 m 2 / g], Asahi #50HG [Nitrogen adsorption specific surface area: 20m 2 / g], Asahi #52 [Nitrogen adsorption specific surface area: 28 m 2 / g], Asahi #51 [Nitrogen adsorption specific surface area: 20 m 2 / g], Asahi #50U [Nitrogen adsorption specific surface area: 27 m 2 / g], Asahi #50 [Nitrogen adsorption specific surface area: 23 m 2 / g], Asahi #35 [Nitrogen adsorption specific surface area: 24 m 2 / g], Asahi #22K [Nitrogen adsorption specific surface area: 21 m 2 / g], Asahi #15HS [Nitrogen adsorption specific surface area: 14 m 2 / g], Asahi #15 [Nitrogen adsorption specific surface area: 12 m 2 / g], Asahi #8 [Nitrogen adsorption specific surface area: 12 m 2 / g], Asahi Thermal [Nitrogen adsorption specific surface area: 24 m 2 / g]
[0040] One or more of these carbon blacks can be used. In particular, as the carbon black, it is preferable to use furnace black such as SAF, ISAF, HAF, MAF, FEF, GPF, or SRF. <Carbon black ratio> As mentioned above, the proportion of carbon black is limited to 60 parts by mass or more and 90 parts by mass or less per 100 parts by mass of the total amount of rubber.
[0041] If the proportion of carbon black is less than this range, the rubber hardness of the cross-linked product forming the fender cannot be made sufficiently large, and it may not be possible to accommodate larger ships, etc., or to ensure good cushioning performance when the fender is made smaller. On the other hand, when the proportion of carbon black exceeds the above range, even if the specific ethylene-α-olefin copolymer rubber is blended in the above-mentioned specified proportion, the viscosity of the rubber composition for fenders before crosslinking may increase and the processability may decrease.
[0042] In addition, the elongation of the crosslinked material may become small, making it impossible to provide the fender with good shock-absorbing properties. In contrast, by setting the proportion of carbon black within the above-mentioned range, a fender can be formed which is made of a cross-linked product having even greater rubber hardness and which also has excellent shock-absorbing performance, and a rubber composition for a fender which has even better processability can be obtained.
[0043] In order to further improve this effect, even within the above range, the proportion of carbon black is preferably at least 65 parts by mass, and particularly preferably at least 70 parts by mass, per 100 parts by mass of the total amount of rubber, and is preferably at most 85 parts by mass, and particularly preferably at most 80 parts by mass. When two or more types of carbon black are used in combination, the total proportion thereof should be within the above range.
[0044] <Crosslinking component> Examples of the crosslinking component for crosslinking the rubber include a crosslinking agent and a crosslinking accelerator. (Crosslinking agent) Examples of the crosslinking agent include sulfur-based crosslinking agents and peroxide-based crosslinking agents, with sulfur-based crosslinking agents being particularly preferred.
[0045] Examples of the sulfur-based crosslinking agent include powdered sulfur, powdered sulfur in oil, precipitated sulfur, colloidal sulfur, dispersible sulfur, and other sulfur-containing organic compounds such as tetramethylthiuram disulfide and N,N-dithiobismorpholine, with sulfur being particularly preferred. The proportion of sulfur can be set arbitrarily, but is preferably at least 0.5 parts by mass and at most 2 parts by mass per 100 parts by mass of the total amount of rubber.
[0046] If the proportion of sulfur is less than this range, the crosslinking rate of the rubber composition for a fender as a whole becomes slow, and the time required for crosslinking becomes long, which may result in a decrease in productivity of the fender. Furthermore, if the proportion of sulfur exceeds the above range, the compression set after crosslinking may become large, or the excess sulfur may bloom on the surface of the fender. When using, for example, oil-containing powdered sulfur, dispersible sulfur, or the like, the above ratio refers to the ratio of sulfur itself as an active ingredient contained therein.
[0047] When an organic sulfur-containing compound is used as a crosslinking agent, the proportion thereof is preferably adjusted so that the proportion of sulfur contained in the molecule per 100 parts by mass of the total amount of rubber falls within the above range. (Crosslinking accelerator) Examples of the crosslinking accelerator include inorganic accelerators such as slaked lime, magnesia (MgO), litharge (PbO), etc., and the following various organic accelerators, which may be used alone or in combination.
[0048] Guanidine accelerators such as 1,3-di-o-tolylguanidine, 1,3-diphenylguanidine, 1-o-tolylbiguanide, and di-o-tolylguanidine salts of dicatechol borate. Thiazole accelerators such as 2-mercaptobenzothiazole and di-2-benzothiazolyl disulfide.
[0049] Sulfenamide accelerators such as N-tert-butyl-2-benzothiazolylsulfenamide and N-cyclohexyl-2-benzothiazolylsulfenamide. Thiuram accelerators such as tetramethylthiuram monosulfide, tetramethylthiuram disulfide, tetraethylthiuram disulfide, and dipentamethylenethiuram tetrasulfide.
[0050] Dithiocarbamate accelerators such as zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate, and zinc dibutyldithiocarbamate. Thiourea accelerators such as N,N'-diphenylthiourea, trimethylthiourea, and N,N'-diethylthiourea. The proportion of the crosslinking accelerator can be set arbitrarily depending on the type, but in general, it is preferably 0.2 parts by mass or more and 5 parts by mass or less individually per 100 parts by mass of the total amount of rubber.
[0051] <others> The rubber composition for fenders may further contain fillers other than carbon black, antioxidants, crosslinking assistants, plasticizers, waxes, colorants, tackifiers, etc. in any proportion, as required. (Other fillers) Examples of fillers other than carbon black include silica.
[0052] (Anti-aging agent) The antioxidant may be one or more of various antioxidants classified according to their main functions, such as weather-resistant antioxidants and heat-resistant antioxidants. Examples of the antioxidant include N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine and 2,2,4-trimethyl-1,2-dihydroquinoline polymers.
[0053] In particular, N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine is preferred because of its excellent effect of preventing sunlight cracking, ozone cracking, and flex cracking. The proportion of the antioxidant is preferably 0.5 parts by mass or more and 7 parts by mass or less per 100 parts by mass of the total amount of rubber. (Crosslinking aid) Examples of the crosslinking aid include one or more of metal compounds such as zinc oxide; fatty acids such as stearic acid, oleic acid, cottonseed fatty acid, and other conventionally known crosslinking aids.
[0054] The proportion of each crosslinking aid is preferably at least 0.5 parts by mass and at most 7 parts by mass per 100 parts by mass of the total amount of rubber. (Plasticizer) The plasticizer may be, for example, oil or liquid rubber. Among these, the oil may be, but is not limited to, one or more of various grades of oil such as Diana (registered trademark) process oil PW, NH, NP, NS, NR, NM, AC, and AH manufactured by Idemitsu Kosan Co., Ltd.
[0055] Examples of the liquid rubber include one or more of liquid isoprene rubber, hydrogenated liquid isoprene rubber, liquid butadiene rubber, liquid styrene butadiene rubber, and end-modified products thereof. The proportion of the plasticizer is preferably at least 1 part by mass, particularly preferably at least 3 parts by mass, and is preferably at most 30 parts by mass, particularly preferably at most 13 parts by mass, per 100 parts by mass of the total amount of rubber.
[0056] (wax) Examples of waxes include, but are not limited to, OZOACE (registered trademark) 0355 manufactured by Nippon Seiro Co., Ltd., and SANNOC (registered trademark), SANNOC N, and SANNOC P manufactured by Ouchi Shinko Chemical Industry Co., Ltd. These waxes function in combination with antioxidants to prevent sun cracking and ozone cracking.
[0057] The proportion of the wax is preferably at least 0.5 parts by mass and at most 5 parts by mass per 100 parts by mass of the total amount of rubber. The rubber composition for fenders can be prepared, for example, by first kneading the above-mentioned components other than the crosslinking component using a kneader, Banbury mixer or the like, and then adding and kneading the crosslinking component.
[0058] <Physical Properties of Rubber Composition for Fender> The rubber composition for fenders prepared complies with the Japanese Industrial Standard JIS K6300-1. :2013 The Mooney viscosity ML(1+4) at 130°C measured by the method specified in "Unvulcanized rubber - Physical properties - Part 1: Determination of viscosity and scorch time using a Mooney viscometer" is preferably 60 or less, particularly 50 or less.
[0059] If the Mooney viscosity exceeds the above range, processability decreases, and it may become difficult to knead each component to prepare the rubber composition for a fender, or to knead or mold the prepared rubber composition for a fender. In particular, the viscosity of the rubber composition for fenders increases, which may cause problems such as increased heat generation during molding and increased susceptibility to scorching.
[0060] In contrast, by setting the Mooney viscosity within the above range, it is possible to maintain a state in which it is easy to knead the components to prepare the rubber composition for a fender, and to knead and mold the prepared rubber composition for a fender, thereby improving the processability of the rubber composition for a fender. In order to finely adjust the Mooney viscosity within the above range, the type and amount of ethylene-α-olefin copolymer rubber, carbon black, oil, etc. may be adjusted.
[0061] In addition, it is preferable that the crosslinked product of the rubber composition for a fender satisfies the following rubber physical properties. · Japanese Industrial Standard JIS K6253-3 :2012 Type A durometer hardness as specified in "Vulcanized rubber and thermoplastic rubber - Determination of hardness - Part 3: Durometer hardness" is A73 or more and A85 or less. · Japanese Industrial Standard JIS K6251 :2017 The tensile strength T specified in "Vulcanized rubber and thermoplastic rubber - Determination of tensile properties" is 16 MPa or more, especially 20 MPa or more. The above JIS K6251 :2017 The elongation at break E is defined as b is over 350%, especially over 400%. · Japanese Industrial Standard JIS K6262 :2013 The compression set CS specified in "Vulcanized rubber and thermoplastic rubber - Determination of compression set at room temperature, high temperature and low temperature" is 30% or less, especially 20% or less.
[0062] This makes it possible to appropriately balance the above-mentioned physical properties of the rubber and impart good shock-absorbing performance to the fender. The process for producing a fender using the prepared rubber composition for fenders may be the same as in the conventional process. That is, the fender can be produced by combining any steps such as molding, sheet molding, assembly, and crosslinking depending on the size and shape of the fender to be produced.
[0063] 《Fender》 At least a part of the fender of the present invention, for example a support leg which is fixed to a quay or the like and elastically deforms when a ship or the like comes alongside, is made of the crosslinked product of the rubber composition for fenders of the present invention. Specific examples of the fender of the present invention include the following various fenders. An arch-shaped fender (including so-called inverted V-shaped, lambda (λ)-shaped and beta (β)-shaped) in which a head portion that constitutes the flat impact surface against which a ship or the like comes alongside, and a pair of support legs that hang down while spreading out in the fore-and-aft direction from the head portion are integrally formed from a cross-linked product of a rubber composition for fenders. A so-called kappa (κ) type fender in which a disk-shaped head and a truncated cone-shaped support leg that hangs down while expanding radially from the head are integrally formed by a cross-linked product of a rubber composition for fenders. A so-called π-type fender comprising a head portion made of steel or the like and a pair of support legs made of a cross-linked product of a rubber composition for fenders that hang down from the head portion while spreading out in the front-to-rear direction.
[0064] In any of these fenders, by forming the support legs and the like from the cross-linked product of the rubber composition for fenders of the present invention described above, good shock-absorbing performance can be maintained even if the proportion of carbon black is increased to increase the rubber hardness of the cross-linked product. Therefore, it is possible to accommodate the increase in size of ships, etc., and to ensure good cushioning performance when the fender is made smaller. EXAMPLES
[0065] The present invention will be further described below based on examples and comparative examples, but the configuration of the present invention is not necessarily limited to these examples. Example 1 (Preparation of Rubber Composition for Fender) The rubber used was a combination of 5 parts by mass of a specific ethylene-α-olefin copolymer rubber, EBDM with an ethylene content of 77% by mass (Mitsui EPT K-9720 manufactured by Mitsui Chemicals, Inc., as mentioned above, ethylene content: 77% by mass, diene content: 10.4% by mass), and 95 parts by mass of natural rubber (TSR20 product).
[0066] A total of 100 parts by mass of both rubbers was kneaded together with the components shown in Table 1 below using a 3 L kneader.
[0067] [Table 1]
[0068] The components in Table 1 are as follows. The parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. Carbon black (i): HAF, the aforementioned Tokai Carbon Co., Ltd.'s Seast 3, nitrogen adsorption specific surface area: 79 m 2 / g Carbon black (ii): GPF, the aforementioned Tokai Carbon Co., Ltd.'s Seast V, nitrogen adsorption specific surface area: 27 m 2 / g Crosslinking aid I: Zinc oxide type 2, manufactured by Mitsui Mining & Smelting Co., Ltd. Crosslinking aid II: stearic acid, trade name Tsubaki manufactured by NOF Corporation Antioxidant: N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine, Nocrac (registered trademark) 6C manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Wax: Sannock, manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Oil: Diana Process Oil NH-70S manufactured by Idemitsu Kosan Co., Ltd. Next, the crosslinking components shown in Table 2 below were added, and the mixture was further kneaded using an open roll to prepare a rubber composition for a fender.
[0069] [Table 2]
[0070] The components in Table 2 are as follows. The parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. Crosslinking agent: Kinkajirushi 5% oil-filled fine sulfur manufactured by Tsurumi Chemical Industry Co., Ltd. Accelerator NS: N-tert-butyl-2-benzothiazolyl sulfenamide, a sulfenamide-based accelerator, Noccela (registered trademark) NS manufactured by Ouchi Shinko Chemical Industry Co., Ltd. The proportion of EBDM was 5 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of the two types of carbon black in total was 80 parts by mass per 100 parts by mass of the total amount of rubber.
[0071] Example 2 A rubber composition for a fender was prepared in the same manner as in Example 1, except that the amount of EBDM was 10 parts by mass, the amount of natural rubber was 90 parts by mass, the amount of carbon black (i) was 55 parts by mass, and the amount of carbon black (ii) was 25 parts by mass. The proportion of EBDM was 10 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of the two types of carbon black in total was 80 parts by mass per 100 parts by mass of the total amount of rubber.
[0072] Example 3 A rubber composition for a fender was prepared in the same manner as in Example 1, except that the amount of EBDM was 20 parts by mass and the amount of natural rubber was 80 parts by mass. The proportion of EBDM was 20 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of the two types of carbon black in total was 80 parts by mass per 100 parts by mass of the total amount of rubber.
[0073] Example 4 A rubber composition for a fender was prepared in the same manner as in Example 1, except that 30 parts by mass of EPDM having an ethylene content of 70% by mass [the above-mentioned Nordel IP4770P manufactured by Dow Chemical Company, ethylene content: 70% by mass, diene content: 4.9% by mass] and 70 parts by mass of natural rubber (TSR20 product) were used in combination as the rubber, and the amount of carbon black (i) was 55 parts by mass and the amount of carbon black (ii) was 25 parts by mass.
[0074] The proportion of EPDM was 30 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of the two types of carbon black in total was 80 parts by mass per 100 parts by mass of the total amount of rubber. Example 5 A rubber composition for a fender was prepared in the same manner as in Example 1, except that 20 parts by mass of EPDM having an ethylene content of 66% by mass (the aforementioned Esprene 512F manufactured by Sumitomo Chemical Co., Ltd., ethylene content: 65% by mass, diene content: 4.0% by mass) and 80 parts by mass of natural rubber (TSR20 product) were used in combination as the rubber.
[0075] The proportion of EPDM was 20 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of the two types of carbon black combined was 80 parts by mass per 100 parts by mass of the total amount of rubber. Comparative Example 1 A rubber composition for a fender was prepared in the same manner as in Example 1, except that 30 parts by mass of SBR (JSR 1502, non-oil extended, manufactured by JSR Corporation) and 70 parts by mass of natural rubber (TSR20 product) were used in combination as the rubber, 90 parts by mass of carbon black (i) alone was blended as the carbon black, and the amount of oil was 10 parts by mass.
[0076] The proportion of EPDM was 0 part by mass per 100 parts by mass of the total amount of rubber, and the proportion of carbon black was 90 parts by mass per 100 parts by mass of the total amount of rubber. Comparative Example 2 A rubber composition for a fender was prepared in the same manner as in Example 1, except that 30 parts by mass of EPDM having an ethylene content of 63% by mass [Esprene 524 manufactured by Sumitomo Chemical Co., Ltd., ethylene content: 63% by mass, diene content: 4.5% by mass] and 70 parts by mass of natural rubber (TSR20 product) were used in combination as the rubber, and the amount of carbon black (i) was 55 parts by mass and the amount of carbon black (ii) was 25 parts by mass.
[0077] The proportion of EPDM was 30 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of the two types of carbon black in total was 80 parts by mass per 100 parts by mass of the total amount of rubber. Comparative Example 3 A rubber composition for a fender was prepared in the same manner as in Example 1, except that 30 parts by mass of EPDM having an ethylene content of 50% by mass [Esprene 505A manufactured by Sumitomo Chemical Co., Ltd., ethylene content: 50% by mass, diene content: 9.5% by mass] and 70 parts by mass of natural rubber (TSR20 product) were used in combination as the rubber, and the amount of carbon black (i) was 55 parts by mass and the amount of carbon black (ii) was 25 parts by mass.
[0078] The proportion of EPDM was 30 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of the two types of carbon black in total was 80 parts by mass per 100 parts by mass of the total amount of rubber. Comparative Example 4 A rubber composition for a fender was prepared in the same manner as in Example 1, except that 40 parts by mass of EPDM having an ethylene content of 66% by mass (the aforementioned Esprene 512F manufactured by Sumitomo Chemical Co., Ltd., ethylene content: 65% by mass, diene content: 4.0% by mass) and 60 parts by mass of natural rubber (TSR20 product) were used in combination as the rubber, and no oil was added.
[0079] The proportion of EPDM was 40 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of the two types of carbon black in total was 80 parts by mass per 100 parts by mass of the total amount of rubber. <Mooney Viscosity Test> The Mooney viscosity ML(1+4)130°C of the rubber composition for fenders prepared in each Example and Comparative Example was measured according to the Japanese Industrial Standard JIS K6300-1. :2013The measurements were performed according to the method specified in "Unvulcanized rubber - Physical properties - Part 1: Determination of viscosity and scorch time using a Mooney viscometer."
[0080] Mooney viscosity ML(1+4)130°C was evaluated as "x" if it was over 60, as "good" if it was over 50 and not more than 60, and as "good" if it was not more than 50. Preparation of samples The rubber compositions for fenders prepared in each of the Examples and Comparative Examples were press-molded at 140° C. for 60 minutes and crosslinked to prepare sheet-shaped samples having a thickness of 2 mm.
[0081] <Rubber hardness test> Three sheets of the prepared sheet samples were stacked together and tested according to the Japanese Industrial Standard JIS K6253-3 :2012 A test piece was prepared as specified in "Vulcanized rubber and thermoplastic rubber - Determination of hardness - Part 3: Durometer hardness" and the value after 3 seconds was read at the standard test temperature in accordance with the measurement method specified in the same standard, which was taken as the Type A durometer hardness.
[0082] The type A durometer hardness was evaluated as "○" when it was A73 or more and A85 or less, and as "×" otherwise. Tensile Test The sheet samples were punched out and tested according to the Japanese Industrial Standard JIS K6251. :2017 Dumbbell-shaped No. 3 test pieces were prepared as specified in "Vulcanized rubber and thermoplastic rubber - Determination of tensile properties" and tensile tests were performed at standard test temperatures as specified in the same standard to determine the tensile strength T (MPa) and elongation at break Eb (%).
[0083] The tensile strength T was evaluated as follows: less than 16 MPa was evaluated as "x", 16 MPa or more but less than 20 MPa was evaluated as "○", and 20 MPa or more was evaluated as "◎". The elongation at break Eb was evaluated as follows: less than 350% was evaluated as "x", 350% or more but less than 400% was evaluated as "◯", and 400% or more was evaluated as "◎". <Compression set test> The rubber compositions for fenders prepared in each of the Examples and Comparative Examples were mold-vulcanized and tested according to the Japanese Industrial Standard JIS K6262 :2013Large test pieces were prepared as specified in "Vulcanized rubber and thermoplastic rubber - Determination of compression set at room temperature, high temperature, and low temperature" and subjected to the compression set test as specified in the same standard to determine the compression set CS (%) after 24 hours at 70℃.
[0084] Compression set CS (%) was evaluated as "x" if it was over 30%, as "good" if it was over 20% to 30% or less, and as "good" if it was 20% or less. The above results are shown in Tables 3 and 4.
[0085] [Table 3]
[0086] [Table 4]
[0087] From the results of Examples 1 to 5 and Comparative Examples 1 to 4 in Tables 3 and 4, it was found that by including a specific ethylene-α-olefin copolymer rubber having an ethylene content of 65 to 80 mass% in a ratio of 3 to 35 parts by mass per 100 parts by mass of the total amount of rubber, it is possible to prevent the viscosity of the rubber composition for fenders from increasing and the processability from decreasing, even if the ratio of carbon black is set to 60 to 90 parts by mass per 100 parts by mass of the total amount of rubber in order to increase the rubber hardness of the cross-linked product.
[0088] It was also found that by including the specific ethylene-α-olefin copolymer rubber in the above-mentioned predetermined ratio, it is possible to appropriately balance the rubber properties of the cross-linked product even when the ratio of carbon black is within the above-mentioned range, thereby imparting good cushioning performance to the fender. Furthermore, from the results of Examples 1 to 5, it was found that the ethylene-α-olefin copolymer rubber is a copolymer rubber further containing a diene, the α-olefin is preferably propylene or butene, and the rubber is preferably one of two types: ethylene-α-olefin copolymer rubber and natural rubber.
Claims
1. Crosslinkable rubber, 60 parts by mass or more and 90 parts by mass or less of carbon black per 100 parts by mass of the total amount of the rubber; and A cross-linking component for cross-linking the rubber, The rubber includes an ethylene-α-olefin copolymer rubber having an ethylene content of 65% by mass or more and 80% by mass or less, The ethylene-α-olefin copolymer rubber is selected from ethylene-propylene copolymer rubber (EPM), ethylene-butene copolymer rubber (EBR), ethylene-octene copolymer rubber (EOR), ethylene-propylene-butene copolymer rubber (EPBR), ethylene-propylene-diene copolymer rubber (EPDM), ethylene-butene-diene copolymer rubber (EBDM), and ethylene-propylene-butene-diene copolymer rubber (EPBDM), The rubber composition for fenders uses a sulfur-based crosslinking agent as the crosslinking component (excluding the case where the rubber composition contains a peroxide as a vulcanizing agent, zinc acrylate or zinc methacrylate as a co-crosslinking agent, and further contains liquid polybutadiene).
2. A rubber composition for a fender comprising a cross-linkable rubber, 60 parts by mass or more and 90 parts by mass or less of carbon black per 100 parts by mass of the total amount of the rubber, and a cross-linking component for cross-linking the rubber, wherein the rubber contains an ethylene-α-olefin copolymer rubber having an ethylene content of 65% by mass or more and 80% by mass or less in an amount of 3 parts by mass or more and 35 parts by mass or less per 100 parts by mass of the total amount of the rubber, A rubber composition for a fender, the type A durometer hardness of which when crosslinked is A73 or more and A85 or less.
3. 3. The rubber composition for a fender according to claim 1, wherein the rubber is two kinds of rubber, the ethylene-α-olefin copolymer rubber and natural rubber.
4. 4. The rubber composition for a fender according to claim 1, which has a Mooney viscosity ML(1+4) at 130° C. of 60 or less.
5. A rubber composition for fenders described in any one of claims 1 to 4, wherein the proportion of carbon black is 65 parts by mass or more and 90 parts by mass or less per 100 parts by mass of the total amount of rubber.
6. 6. The rubber composition for a fender according to claim 1, wherein the crosslinked product has a tensile strength T of 16 MPa or more.
7. 7. The rubber composition for a fender according to claim 1, wherein the crosslinked product has an elongation at break Eb of 350% or more.
8. A fender, at least a part of which is made of a crosslinked product of the rubber composition for a fender according to any one of claims 1 to 7.
Citation Information
Patent Citations
Rubber composition
JP1995188463A
Rubber composition for tire sidewall
JP1998265623A
Vibration-proof rubber composition and vibration-proof rubber
JP2012117004A
Rubber composition for fender
JP2016222830A
Rubber composition
WO2019163870A1